Gender differences in climate-smart adaptation practices amongst bean-producing farmers in Malawi: The case of Linthipe Extension Planning Area - Nchanji, Eileen Bogweh; Kabuli, Hilda; Onyango, Nyamolo; Cosmas, Lutomia K.; Chisale, Virginia; Matumba, Anne (Frontiers Media, 2022)
Agriculture is amongst the vulnerable sectors to climate change and its associated impacts. Most women are more vulnerable to the impacts of climate change than men. Climate Smart Agriculture ensures increased productivity thereby enabling food security, income security and wealth creation amongst the farming households. A study was carried out to understand the gender differences in access and use of climate-smart agriculture, challenges and solutions that men and women farmers use to adapt to climate change. Data was collected from 246 randomly sampled households from 14 villages at Linthipe Extension Planning in Dedza district in Malawi. The multivariate probit model was employed to understand the influence of sociodemographic, farm-level, and institutional factors in the application of climate-smart agriculture in the study area. Findings from this study indicate that there are differences in the adoption and use of climate-smart agriculture technologies in bean production amongst different gender categories. More women compared to men and youths tend to use fertilizer, use improved seeds and plant early in order to mitigate and adapt to climate change. Most men adopt and use irrigation, whilst the youth mostly adopted and used pesticides and conservation agriculture practices. The study recommends policies that would ensure the promotion of gender-responsive climate-smart agriculture technologies, improved access to inputs, and capacity building through training.